1973
DOI: 10.1136/jcp.26.8.623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a tanned red cell technique for thyroid microsomal antibodies

Abstract: A haemagglutination test for thyroid microsomal (cytoplasmic) antibodies, using formolized tanned sheep red cells, is described and evaluated. The technique is essentially similar to the thyroglobulin tanned red cell test. It has been shown to be more sensitive and easier to use than the complement-fixation test. A combined screening test to detect both thyroglobulin and microsomal antibodies is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 4 publications
2
16
0
1
Order By: Relevance
“…Our previous reports (4,18) indicated that the MCHA test is more useful than the thyroglobulin hemagglutination antibody (TGHA) test to detect the autoimmune thyroid abnormality. Furthermore, the MCHA test is more sensitive than the complement-fixation test (19). These may be the main factors influencing the good association observed in this series.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous reports (4,18) indicated that the MCHA test is more useful than the thyroglobulin hemagglutination antibody (TGHA) test to detect the autoimmune thyroid abnormality. Furthermore, the MCHA test is more sensitive than the complement-fixation test (19). These may be the main factors influencing the good association observed in this series.…”
Section: Discussionmentioning
confidence: 94%
“…Antithyroglobulin and antimicrosomal antibodies were determined by hemagglutination, using reagent kits from Fujizoki, Tokyo. 4 Values are expressed as means ± SEM. Statistical analysis was done by Student's t test for paired and unpaired data as appropriate and chi square test.…”
Section: Methodsmentioning
confidence: 99%
“…The latter individual was retained in the analysis because she also had ANA. 23 Thyroglobulin and microsomal thyroid antibodies were sought in 152 patients (98%) by standard techniques [24][25][26] and a titer of at least 1:100 was considered positive.…”
Section: Methodsmentioning
confidence: 99%